The benefits of reading skills in the educational process - G. Amirova (Proceedings of The ICECRS, 2019)
The aim of this article is to give all advantages of using reading skills in learning and their effect teaching process, to give useful and vital information about the advantages of reading. In this case, the benefits of reading skills in the educational process of the research have been pinpointed as the whole. In conclusion, research has been finalizing outcomes and drawbacks as the major points of the development.